SPIRITUAL VALUES FORMATION OF PROFESSIONAL CULTURE OF LEADING PERSONNEL: SOLUTIONS AND PROBLEMS - Ikramjon Batirovich Masharipov, (INTERNATIONAL JOURNAL OF SOCIAL SCIENCE & INTERDISCIPLINARY RESEARCH ISSN: 2277-3630 Impact factor: 8.036, 2024)
In this article, the role of spiritual values in the development of the professional culture of leaders, the aspect that expresses the human essence, the special form and existence of existence, an important factor in their political activity, the formation, development, and refinement of human thinking as a result of creative work is also important in the political activity of leaders as a social phenomenon. it is revealed that the improvement of the material living conditions of a person is inextricably linked with his spiritual worldview by giving priority to spiritual wealth over material wealth. A nation can never achieve economic and socio-political development with spiritual poverty. Spirituality has a place in any development. The higher the spirituality, the higher the effectiveness and productivity of the work. Human potential is the most active, most creative factor, which, together with professional culture, provides fundamental changes. Analytical comments of the author are formed based on the fact that through spirituality, people and the nation clearly understand the meaning and essence of the work being done, they can turn their work into a factor of joy and development, and their other political activities